When writing about wine: how ratings impact reviews. (2nd October 2019) - Lam, Joey; Lambrechts, Maryke; Pitt, Christine; Afsharipour, Afshin
ABSTRACT: This paper investigated whether the nature of the language in wine reviews differs by wine ratings. Reviews of 1-, 3- and 5-star wines were downloaded into text files, then analyzed for Word Count, Analytic, Clout, Authentic and Tone by using LIWC text analysis. ANOVAS was adopted to determine differences between reviews by ratings. There were significant differences between wines by star rating on Word Count, Analytic, and Tone, while there were no significant differences on Clout and Authenticity. This research was limited to South African wines, 1-, 3- and 5-star reviews. It was not possible to identify all individual reviewers. Also, price and availability were not considered. Research implications include using other textual analysis software to conduct inter-reviewer comparison of reviews with the same ratings by different influential wine writers, investigating price as a variable in rating and review, and authenticity as a factor in the context. Wine marketers can help wine makers gain a better understanding of what tastemakers prefer by analyzing wine reviews with automated text analysis software such as LIWC. A positive link between word count in a wine review, the degree of analysis and tone used with the ratings of wines by experts can be established.